Breaking the vicious circle: Experiences of people in chronic pain on the pain rehabilitation journey - Hafdís Skúladóttir; Thora J. Gunnarsdóttir; Sigríður Halldórsdóttir; Herdís Sveinsdóttir; Janean E. Holden; Amalía Björnsdóttir (Nursing Open, 2020)
Abstract Aim To explore the lived experience of individuals' in chronic pain of participating in a pain rehabilitation programme in Iceland. Design Phenomenological research. Method The Vancouver School of Doing Phenomenology. Eleven participants were interviewed. Results The overarching theme was as follows: “the journey of breaking the vicious circle of chronic pain.” Before the programme, the participants felt they were in survival mode, trying to survive each day; they were stuck in a vicious circle of chronic pain, simultaneously trying to ease and conceal the pain. Reaching out for professional help was a turning point. While attending the programme, participants began deconstructing their old ways of dealing with chronic pain. After completing the programme, they were still reconstructing their daily lives. In conclusion, pain rehabilitation programmes can be the first step towards breaking the vicious circle of chronic pain.